Lung Ultrasound: A New Tool in the Management of Congenital Lung Malformation - Quercia, Michele; Panza, Raffaella; Calderoni, Grazia; Di Mauro, Antonio; Laforgia, Nicola (American Journal of Perinatology, 2019)
Objective This study was aimed to evaluate effectiveness of lung ultrasound (LUS) in the management of congenital pulmonary airway malformation and pulmonary sequestration in NICUs.Study Design This is a nonconsecutive case series of neonates admitted to the academic NICU of Policlinico of Bari, Italy, from 2010 to 2018, for suspected lung malformations and examined by LUS.Results Seven neonates were admitted for suspected pulmonary malformations, four neonates were diagnosed with pulmonary sequestration and three with congenital pulmonary airway malformation either type I (two cases) or type II (one case) according to Adzick classification. Prenatal scans had described lung malformations in six patients. Two underwent surgical intervention during the 1st month of life. All were successfully discharged home and their follow-up has been uneventful thereafter. In all the seven neonates, LUS easily detected the lesion showing a significantly high correspondence with computed tomography (CT) scan findings.Conclusion We described the first case series of neonates affected by complex pulmonary malformations, assessed by LUS. In our experience, LUS was safe and effective for the diagnosis with high degree of consistency with CT scan findings. We suggest that LUS might be an important diagnostic method for lung malformations in newborns and a useful technique for their follow-up and late management, avoiding multiple exposures to radiations.
Keywords: lung ultrasound; congenital pulmonary airway malformation; pulmonary sequestration; congenital diaphragmatic hernia